Знахiдки пломб дрогичинського типу з Києва - Івакін, Г.Ю.; Бібіков, Д.В.; Івакін, В.Г.; Баранов, В.І. (Археологія, 2020)
У статті публікуються нові сфрагістичні матеріали з
давньоруського Києва та його округи, а саме — товарні
пломби т. зв. «дрогичинського типу», які були виявлені
під час науково-рятівних досліджень Архітектурноархеологічної експедиції ІА НАН України протягом
2016—2017 рр. Крім того, наводиться стислий огляд історіографії проблеми. Знахідки пломб з останніх років
досліджень розглядаються у контексті сучасної сфрагістичної науки, класифіковані зображення на пломбах,
робляться спроби їх персональної атрибуції. Пломбы дрогичинского типа остаются наименее изученной категорией древнерусских сфрагистических древностей. В течение 2016—2017 гг. в результате раскопок Архитектурно-археологической экспедиции Института археологии НАН Украины на территории современного Киева найдено 29 подобных предметов и заготовок под них — больше, чем за все предыдущие годы раскопок города. Большая часть найденных пломб относится к неизвестным ранее
видам. Однако, отличаясь относительной сложностью сфрагистичних типов, они находят близкие аналогии среди
синхронных актовых печатей. Все достаточно надежно атрибутированные пломбы датируются второй половиной
ХІ — первой половиной XII вв. Они принадлежат великим князьям киевским Изяславу Ярославичу, Святославу
Ярославичу, ВсеволодуЯрославичу,Святополку, Всеволоду Ольговичу, а также сынуИзяслава—князю Волынскому
и Туровскому Ярополку. По мнению авторов, раскопками обнаружены самые ранние экземпляры пломб дрогичинского типа. Особенно репрезентативными являются находки из раскопок на Подоле по ул. Кирилловской, 37, где в
указанный период, вероятно, функционировала великокняжеская таможня на северном въезде в Киев. Drohychyn type lead seals remain poorly studied among Old Rus sphragistics. There is no consensus among researchers
regarding both the functions they performed and the personal attribution of specific types of seals. On the territory of modern
Kyiv 28 items of lead seals and blanks were discovered during 2016—2017 excavations of Architectural and Archaeological
expedition of the Institute of Archaeology, the National Academy of Sciences of Ukraine. These include more than were
116 ISSN 0235-3490 (Print), ISSN 2616-499X (Online). Археологія, 2020, № 2
discovered during all the previous years of excavations in the city. The finds come from three points: the northwestern part
of Kyiv Podil, the newly discovered settlement Feofaniia 2 and the settlement of Kytaiv fortress. The vast majority of the
excavated seals represent unknown types. However, despite relative complexity of the sphragistic types, they show close
analogies among synchronous bullae. This allows not only classifying the images on the seals, but also making an attempt of
their personal attribution. All studied items are dated by the second half of XI — early XII centuries. They belong to Kyivan
Grand Princes Iziaslav Yaroslavych, Sviatoslav Yaroslavych, Vsevolod Yaroslavych, Sviatopolk Iziaslavych, Vsevolod
Olhovych, as well as Iziaslav’s son, Yaropolk, prince of Volhynia and Turov. To our opinion, excavations discovered the
earliest Drohychyn type lead seals. The most representative finds were excavated in Podil (Kyrylivska Street, 37), where
probably customs of Great Prince in old times were located (at the northern entry to the city). Their topography confirms
the point of view on lead seals, as on credentials associated with Old Rus “fur money”. The published collection should form
the basis of a common catalogue of sphragistic finds from the territory of Kyiv and its environs.